IDEOLOGI DAN PRAKTIK KEAGAMAAN MAHASISWI BERCADAR DI PTKI SE-KOTA METRO - Masrurotul Mahmudah; Ambariyani Ambariyani; Binti Khoiriyah; Muhamad Agus Mushodiq (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
This research aims to uncover the identity of the ideology and practices of the religious Sorority PTKI Se-Metro City about hijab. This important research is done because of the assumption that the use of certain types of hijab is the symbol of extremism and radicalism. First, the existence of the facts users Hijab and veil that are involved in terrorism. In this study, the researchers used a qualitative research method. Data networking is done by the method of conversing and listening. Researchers conduct interviews and record the results of the interviews in the form of sound or video. As for the theory used in exposing the identity of the ideology and practice of religious students about the veil is a religious dimension to the Glock and Stark. As for the findings from this research are (1) the use of the veil distributed by the ideology of syncretism that fall into the category of space in between. But the identity of the space in between is so potentially could be changed, both moved on to understand the extreme about hijab and veil or more moderate in understanding that the veil is not a compulsory subject. (2 user veil that has extreme religious ideology of familiar and has been crystallized. Students who have learned not to mention could have contested the pattern she thought. But in their religious practice has three types of practices, syncretism, moderate and extreme in understanding hijab.